Grappling with Cultural Sensitivity of Culturally Specific Concepts in English-Arabic Medical Texts - Al-Ahdal, Saddam Ahmed; Alqasham, Fahd Hamad (International Journal of Language and Literary Studies, 2025)
Problems relating to cultural aspects, linguistic differences and religious implications can complicate medical language communication. The present study delves into the challenges of translating culturally specific medical concepts between English and Arabic, focusing on cultural sensitivity in medical translation. The need to explore this area in the context of English for Specific Purposes (ESP) stems from the needs of the majorly multicultural-multilingual social fabric of modern Saudi Arabia. The study uses a random corpus of fifty medical prescriptions in English and their human-translated Arabic versions for detailed analysis. The corpus are then analyzed for four features: Cultural Sensitivity and Appropriateness, Direct Equivalents, Medical Practices and Beliefs, and Translating Specific Medical Terms to establish translation efficacy. Content analysis by medical translation experts revealed that of the four areas under study, ensuring cultural sensitivity and appropriateness was least assured in the translation of medical prescriptions. Semi-structured interviews with a smaller set of translators helped identify the challenges in translation and some recommendations for tackling them. The study is likely to transform the focus and curriculum of ESP and translation courses in Saudi Arabia as well as other similar multicultural-multilingual environments healthcare services focus on effective language strategies and communication. Finally, the identification of the key problems and issues will contribute to optimizing the experience towards building culturally grounded medical language translation practices.